Pengaruh Intelegensi Quotient (IQ), Emotional Quotient (EQ) dan Beban Kerja terhadap Kualitas Pelayanan Tenaga Perawat - Wahyuni, Hari; Erwantiningsih, Eni (Jurnal Manajemen dan Kewirausahaan, 2020)
This research aims to determine the effect of Intelligence Quotient (IQ), Emotional quotient (EQ) and workload to the quality of nurses' services at Puskesmas in Pasuruan. This type of research is quantitative research. The populations of this research are 80 nurses at Puskesmas in Pasuruan and all taken as a sample. The technique data analysis of this research is a multiple linear regression test. The result of this research indicates that the Intelligence Quotient (IQ) influences the quality of nurses' service in Pasuruan city, while the Emotional Quotient (EQ) and workload do not influence the quality of nurses in Pasuruan city.https://doi.org/10.26905/jmdk.v8i1.3846Â